25-9 Beacon Street, 1930 - Conlin (Tufts Archival Research Center, 2005)
Street-level view north of (left to right) 25-9 Beacon Street. The Boston School Committee Building at 15 Beacon Street is the center building in the photograph. The Lawyers Building is located to the northeast of the Boston School Committee Building, at 9-11 Beacon Street. The Hotel Bellevue, at 25 Beacon Street and the corner of Freeman Place, is located to the southwest of 15 Beacon Street. All three buildings are draped in bunting to celebrate Boston's tercentenary, while American flags (with only 48 stars) hang from the windows of 15 Beacon Street. Wrought iron railing adorns the facade of the Hotel Bellevue. A flag pole is situated in front of the building, while a decorative lamp with Hotel Belleview etched into its glass cover marks the hotel's entrance. Several automobiles are parked along Beacon Street. 1 Somerset Street is included in the background, along the right side of the photograph. Copyprint 7 1/2 x 9 1/2, 8 x 10 overall Photographs